Variable Weights in Assessment of Survival System - Jinhui Zhao (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Weight is one of key parameters in survival assessment. Its veracity will directly affect the final evaluation result. After analyzed the relationships between survival incidents and induced factors, this paper draw into the natural weight, based on impact probability, to dynamically calculate the weights of assessment indexes. Based on membership of susceptible degree, appropriate distribution function is selected to describe the weight change of specific index. Combined with examples, the application process is present in detail. Experiments and analysis show that proposed method can truthfully and objectively reflect the impact of each index on survival system．It is valuable to apply and popularize in a variety of industries. http://dx.doi.org/10.11591/telkomnika.v11i5.2138